2018
DOI: 10.1002/etc.4277
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance response by shrimps to a copper gradient: Does high population density prevent avoidance of contamination?

Abstract: Bioassays using the nonforced exposure approach have been shown to be a relevant tool that might complement the traditional ecotoxicological risk assessment. Because the nonforced exposure approach is based on spatial displacement of organisms and the consequent habitat selection processes, the population density might play an important role in the decision to avoid or prefer an ecosystem. Therefore, the aim of the present study was to assess if the avoidance response to contamination, measured in a nonforced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…These authors observed that among the different lineages tested, the sensitivity and early reactiveness of the organisms to avoid copper was directly related to the lethal sensitivity of the lineages. Other invertebrates such as the cladoceran D. magna (exposed to pulp mill effluents [53]; atrazine [51]; and salinity as stress factor [54]), the freshwater copepod Boeckella occidentalis intermedia (crude oil as the contaminant [55]), the ostracod Heterocypris incongruens (salinity as the stress factor [54]), the gastropod Peringia ulvae (sediment spiked with cadmium [56]), the freshwater shrimp Atyaephyra desmarestii (exposure to copper [39,[57][58][59]), the marine shrimp Litopenaeus vannamei (exposed to copper [60,61]), and the saltmarsh shrimp Palaemon varians (exposed to musks and sunscreens [25,62]) have been tested for avoidance. In general, the avoidance response reported in those studies was more sensitive than the lethal and some sub-lethal endpoints described by other authors (see references cited above).…”
Section: Avoidance: a Repellency-driven Behavioral Responsementioning
confidence: 99%
See 1 more Smart Citation
“…These authors observed that among the different lineages tested, the sensitivity and early reactiveness of the organisms to avoid copper was directly related to the lethal sensitivity of the lineages. Other invertebrates such as the cladoceran D. magna (exposed to pulp mill effluents [53]; atrazine [51]; and salinity as stress factor [54]), the freshwater copepod Boeckella occidentalis intermedia (crude oil as the contaminant [55]), the ostracod Heterocypris incongruens (salinity as the stress factor [54]), the gastropod Peringia ulvae (sediment spiked with cadmium [56]), the freshwater shrimp Atyaephyra desmarestii (exposure to copper [39,[57][58][59]), the marine shrimp Litopenaeus vannamei (exposed to copper [60,61]), and the saltmarsh shrimp Palaemon varians (exposed to musks and sunscreens [25,62]) have been tested for avoidance. In general, the avoidance response reported in those studies was more sensitive than the lethal and some sub-lethal endpoints described by other authors (see references cited above).…”
Section: Avoidance: a Repellency-driven Behavioral Responsementioning
confidence: 99%
“…The effects of density on the avoidance response were tested using the freshwater shrimp A. desmarestii exposed to a copper gradient [57]. The authors employed three different population densities (3, 5 and 10 shrimps per compartment representing 0.5, 0.8, and 1.7 organisms per mL) in a multi-compartmented system.…”
Section: Population Densitymentioning
confidence: 99%